2019
DOI: 10.1002/smll.201902845
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Electrochemical Production of H2O2: Strategies for the Rational Design of High‐Performance Electrocatalysts

Abstract: The production of H2O2 via the electrochemical oxygen reduction reaction (ORR) presents an attractive decentralized alternative to the current industry‐dominant anthraquinone process. However, in order to achieve viable commercialization of this process, a state‐of‐the‐art electrocatalyst exhibiting high activity, selectivity, and long‐term stability is imperative for industrial applications. Herein, an in‐depth discussion on the current frontiers in electrocatalyst design is provided, emphasizing the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(99 citation statements)
references
References 91 publications
2
96
0
1
Order By: Relevance
“…The CO 2 RR activity and spectroscopic results show that the formation of H 2 O 2 is unlikely the cause of the enhanced CO 2 RR performance during the co-electrolysis with O 2 . H 2 O 2 is a possible product of the ORR via the 2-electron pathway 43 . If produced during the co-electrolysis of CO 2 and O 2 on Cu, H 2 O 2 could potentially modify the surface speciation and impact of the rate and product distribution of the CO 2 RR.…”
Section: Resultsmentioning
confidence: 99%
“…The CO 2 RR activity and spectroscopic results show that the formation of H 2 O 2 is unlikely the cause of the enhanced CO 2 RR performance during the co-electrolysis with O 2 . H 2 O 2 is a possible product of the ORR via the 2-electron pathway 43 . If produced during the co-electrolysis of CO 2 and O 2 on Cu, H 2 O 2 could potentially modify the surface speciation and impact of the rate and product distribution of the CO 2 RR.…”
Section: Resultsmentioning
confidence: 99%
“…The pyridinic-N could prevent this effect by occupying the lone pair electrons to form an N-H bond; thus, two-electron pathway occurred in acidic conditions, which was consistent with Refs. [19,20,47]. Although the pyridinic-N exhibited excellent selectivity for two-electron ORR, Strasser et al [45] found that the selectivity would be decreased when the content of nitrogen-doped sites was extremely high.…”
Section: Nitrogen-doped Carbonaceous Materialsmentioning
confidence: 99%
“…[35][36][37] We emphasize that the literature includes a number of high-quality pure experimental studies in the area of 2e-ORR which have been thoroughly addressed in other review papers. [38][39][40][41] However, purely experimental studies are out of the scope of this review paper and our focus herein is on the simulation-based guidance of trends in H 2 O 2 synthesis.…”
Section: Introductionmentioning
confidence: 99%